Lorenzo de' Medici and inheritance law in Florence. Issue 2 (27th May 2019) - Kuehn, Thomas
Abstract: In 1477 a law was passed in Florence concerning inheritance by women. This law has long been taken (including by the near‐contemporaries, Niccolo Machiavelli and Francesco Guicciardini) as Lorenzo de' Medici's effort to preclude his enemies, the Pazzi, from gaining a lucrative estate, just a year before the assassination attempt of Easter 1478. In fact, what the law did was address a real legal problem in the interpretation of Florence's inheritance statute and fit the law with the designs of the Florentine, Giovanni Borromei, whose estate it was, and who seemingly wanted it to go to his nephew. While contemporary consilia reveal that the law's interpretation was a minority position among practising jurists, it was a perfectly legal point of view and not solely a political manoeuvre against the Pazzi.